Comunidades recifais do Arquipélago dos Abrolhos, BA, com ênfase em corais (Cnidaria: Scleractinia e Milleporidae): aspectos metodológicos e comparações entre locais - Ramos, Bárbara Segal (1998)
The quantification of coral communities in three areas in the Abrolhos Archipelago (northern and southern inshore areas in Santa Bárbara Island, and Siriba Island) was performed using quadrats and intercept line transect methods. Colony size and inclination, the distances from random points to the nearest colony and between nearest colonies of the same species were evaluated for the five most frequent or abundant coral species (Agaricia agaricites, Favia gravida, Mussismilia braziliensis, Porites branneri e Siderastrea stellata). No differences were detected in the representation of the community (contributions of different organisms to coverage of an area) when the results of data from quadrats and transects were compared. However, intercept line transects detected more species, presenting higher resolution than quadrats. Dominant reef building organisms, between depths of 1.9 and 4.0 m, were calcareous algae (12.3 to 19.5%) and the coral M braziliensis (1.8 to 24.5%). Several significant differences were found among the three surveyed areas and, in Siriba Island, between different stations of a single area. The main biotic differences among the three areas referred to total coral cover, influence of depth in community structure variation, diversity parameters, colony sizes, and distances from random points to colonies. It is suggested that some of these factors may be affected by physical differences among the three environments.